Staphylococcus aureus cell wall structure and dynamics during host-pathogen interaction. - Joshua A F Sutton; Oliver T Carnell; Lucia Lafage; Joe Gray; Jacob Biboy; Josie F Gibson; Eric J G Pollitt; Simone C Tazoll; William Turnbull; Natalia H Hajdamowicz; Bartłomiej Salamaga; Grace R Pidwill; et al. (PLoS Pathogens)
Peptidoglycan is the major structural component of the Staphylococcus aureus cell wall, in which it maintains cellular integrity, is the interface with the host, and its synthesis is targeted by some of the most crucial antibiotics developed. Despite this importance, and the wealth of data from in vitro studies, we do not understand the structure and dynamics of peptidoglycan during infection. In this study we have developed methods to harvest bacteria from an active infection in order to purify cell walls for biochemical analysis ex vivo. Isolated ex vivo bacterial cells are smaller than those actively growing in vitro, with thickened cell walls and reduced peptidoglycan crosslinking, similar to that of stationary phase cells. These features suggested a role for specific peptidoglycan homeostatic mechanisms in disease. As S. aureus missing penicillin binding protein 4 (PBP4) has reduced peptidoglycan crosslinking in vitro its role during infection was established. Loss of PBP4 resulted in an increased recovery of S. aureus from the livers of infected mice, which coincided with enhanced fitness within murine and human macrophages. Thicker cell walls correlate with reduced activity of peptidoglycan hydrolases. S. aureus has a family of 4 putative glucosaminidases, that are collectively crucial for growth. Loss of the major enzyme SagB, led to attenuation during murine infection and reduced survival in human macrophages. However, loss of the other three enzymes Atl, SagA and ScaH resulted in clustering dependent attenuation, in a zebrafish embryo, but not a murine, model of infection. A combination of pbp4 and sagB deficiencies resulted in a restoration of parental virulence. Our results, demonstrate the importance of appropriate cell wall structure and dynamics during pathogenesis, providing new insight to the mechanisms of disease.